 Erik Jonsson School of Engineering and Computer Science FEARLESS Engineering CS 4384 – 001 Automata Theory Thursday: Context-Free.

Presentation on theme: "Erik Jonsson School of Engineering and Computer Science FEARLESS Engineering CS 4384 – 001 Automata Theory Thursday: Context-Free."— Presentation transcript:

Erik Jonsson School of Engineering and Computer Science FEARLESS Engineering CS 4384 – 001 Automata Theory http://www.utdallas.edu/~pervin Thursday: Context-Free Languages Sections 3.1-3.3 Tuesday 2-25-14 1

Distinguished States 3

4

Context-free Languages Chapter Three 5Tuesday 2-25

Definition A context-free grammar (CFG) G is a quadruple (V, Σ, R, S) where V: a set of non-terminal symbols (Variables) Σ: a set of terminals (V ∩ Σ = Ǿ) (Alphabet) R: a set of rules (R: V → (V U Σ)*) S: a start symbol (a variable)

How do we use rules? If R: A → B, then xAy xBy and we say that xBy is derived from xAy using rule R. If s ··· t, then we write s * t. A string x in Σ* is generated by G=(V,Σ,R,S) if S * x. L(G) = { x in Σ* | S * x}.

Example G = ({S}, {0,1}. {S → 0S1 | ε }, S) ε in L(G) because S ε. 01 in L(G) because S 0S1 01. 0011 in L(G) because S 0S1 00S11 0011. 0 1 in L(G) because S * 0 1. L(G) = {0 1 | n > 0} n n nn n n

Context-free A context-free grammar is “context-free’’ because we can use a rule R no matter what the context. E.g., (M&S P.89, Def. 3.1.2) from the rule R: A -> w, we can derive from the string uAv in one step the string uwv, no matter what the context (that is, for any strings u and v). 9

10

11

12 Palindromes

13 Any positive even number of a’s with any number of b’s anywhere

14

15

16

17

18

19

Parsing Expressions G = (V, ∑, R, E) V = {E, T, F} ∑= {x, 1, 2, +, *, (, )} R = { E -> E + T | T; T -> T * F | F; F -> (E) | x1 | x2 } Expressions, Terms, Factors 20

21

22Parse Tree

Closure Properties 23

24

25

26

Theorem For every regular language L, there exists a CFG G (in fact a Regular Grammar) such that L=L(G). 27

Theorem For every regular language L, there exists a CFG G such that L=L(G). Proof.Let L=L(M) for a DFA M=(Q, Σ, δ, s, F). Construct a CFG G=(V, Σ, R, S) as follows. V = Q, Σ = Σ, R = { q → ap | δ(q, a) = p } U { f → ε | f in F}, S = q0. sq1q1 f=q n x1x1 xnxn S x 1 q 1 x 1 x 2 q 2 ··· x 1 …x n f x 1 …x n 28

29

Regular Grammars 30Note: A -> a is unnecessary

31What's wrong with (ab)*a*?

32

Simplified and Normal Forms 33

Download ppt "Erik Jonsson School of Engineering and Computer Science FEARLESS Engineering CS 4384 – 001 Automata Theory Thursday: Context-Free."

Similar presentations